Pelatihan dan Pendampingan Pengolahan dan Potensi Buah Kelapa menjadi Kopra Putih di Desa Simpang Tiga Daratan Kecamatan Enok - M. Ilham Nur; Andi Herman; Budi; Islahulaili; Intan Sari; Yoyon Riono (PT Ruang Publikasi, 2025)
The implementation of community service activities in Simpang Tiga Daratan Enok Tembilahan Village is motivated by the community's livelihood in the agricultural and plantation sectors with plantation products in the form of Coconuts and Areca Nuts, however, community income in Simpang Tiga Enok Inhil Village is still low due to a lack of innovation in processing plantation products. Coconuts are sold raw to collectors without processing them first so the selling price is low. Therefore, assistance and training is needed for the community in Simpang Tiga Daratan Enok Village to process plantation products. For this reason, this community service activity provided socialization and training on making coconut skullcaps to the people of Simpang Tiga Daratan Enok Inhil Village. There are several programs that will be implemented related to the problems that have been described, namely providing socialization on the use of coconuts to make coconut shells on a national scale, namely coconut shells, providing training on processing coconuts into innovative products and mentoring coconut shell businesses. The response of community leaders and residents to the realization of this training was very positive.